Extracellular Vesicles as Therapeutic Tools for the Treatment of Chronic Wounds - Eric R. Bray; Alisha R. Oropallo; Daniel A. Grande; Robert S. Kirsner; Evangelos V. Badiavas (MDPI AG, 2021)
Chronic wounds develop when the orderly process of cutaneous wound healing is delayed or disrupted. Development of a chronic wound is associated with significant morbidity and financial burden to the individual and health-care system. Therefore, new therapeutic modalities are needed to address this serious condition. Mesenchymal stem cells (MSCs) promote skin repair, but their clinical use has been limited due to technical challenges. Extracellular vesicles (EVs) are particles released by cells that carry bioactive molecules (lipids, proteins, and nucleic acids) and regulate intercellular communication. EVs (exosomes, microvesicles, and apoptotic bodies) mediate key therapeutic effects of MSCs. In this review we examine the experimental data establishing a role for EVs in wound healing. Then, we explore techniques for designing EVs to function as a targeted drug delivery system and how EVs can be incorporated into biomaterials to produce a personalized wound dressing. Finally, we discuss the status of clinically deploying EVs as a therapeutic agent in wound care.